Green Politics (Study on the Regional Regulation of the City of Tasikmalaya Number 2 of 2021 Concerning Domestic Wastewater Management) - Yusriyah, Alya; Yuliawati, Fitriyani; Muchariman, Randi (Epistemik Press, 2025)
Domestic waste water is liquid waste from household activities, as well as other public places that contain materials that can endanger living things and disrupt environmental sustainability. The production of domestic wastewater will increase, especially in densely populated areas, so it is necessary to have initial management of domestic wastewater before it is discharged into the environment around the community. The City of Tasikmalaya itself has issued Regional Regulation Number 2 of 2021 concerning Domestic Wastewater Management. This study aims to analyze how to approach green politics in the Regional Regulation of the City of Tasikmalaya Number 2 of 2021 by using Green Political Theory initiated by R. Eckersley with the ecocentrism paradigm which is the main characteristic in Green Political Theory. The research method used in this research is qualitative research which is descriptive in nature to explain the actual conditions that occur in the field . The results of this study explain that the formation of Regional Regulation of the City of Tasikmalaya Number 2 of 2021 concerning Domestic Wastewater Management is theoretically green politics based on a review of increasing environmental pollution and the achievement of ODF ( Open Defecation Free) in Tasikmalaya City which is still low. So with the formation of this policy to create an ecologically sustainable Tasikmalaya City community that is rooted in concern for the environment , especially in the management of domestic wastewater so as to create healthy and sustainable environmental conditions for the next generation. The management of domestic wastewater is an issue that is closely related to the environment and community activities. Regional Regulation of the City of Tasikmalaya Number 2 of 2021 concerning Domestic Wastewater Management is characteristic of an ecocentric paradigm that adopts a holistic perspective by assessing populations, species, ecosystems and the natural environment as a whole.